Application of fuzzy logic to the optimal location of public utilities: a case study of pedestrian bridges. (2012)
The level of utilization of many public utilities is, most often, influenced by their locations Huge public funds are spent annually on the provision of several public infrastructures, such as pedestrian bridges, that are grossly underutilized due to their poor location or citing. This study was aimed at developing a fuzzy logic based decision support system for the optimal location of pedestrian bridges in a typical Nigerian city. Various factors and their interactions that affect utilization of any pedestrian bridge were identified and characterized. Utilization data on twenty eight existing pedestrian bridges, spread across two states in Nigeria were obtained and analyzed. The triangle and trapezoidal membership function were used to build a fuzzy inference system modeling the dynamics of utilization. The model was tested with the real life data. Four factors: traffic speed, vehicle traffic volume, proximity to market and proximity to bus stop, among other factors, were prominent in influencing utilization level. The model achieves more than 75% accuracy in deciding the suitability of a location based on level of utilization. It is concluded that the fuzzy logic approach is a veritable decision support tool for public facilities location decision problem.